Nghiên cứu cơ chế phản ứng axyl hóa giữa mô hình tương tự nitrocefin với PBP2a bằng phương pháp hóa học lượng tử - Mi, Nguyễn Họa; Kim Phượng, Trần Thị; Ngọc Hồng, Nguyễn Thị; Lâm, Phạm Trọng; Trung, Phạm Quang (Vietnam Journal of Chemistry, 2016)
As shown in our previous reports, nitrocefin has much better strength than methicillin to inhibit PBP2a enzyme of Methicillin-resistant Staphylococcus aureus in acylation reaction. In this study we focus on the inhibition mechanism of nitrocefin-like structures as well as modified nitrocefin (NC1’) in acylation reactions with the PBP2a in order to find the structures with improved inhibition strengths. NC1’ have the six member-ring b-lactam structure as in nitrocefin (NC1), and the substituent group in NC1’ is simple. QM calculations are performed at the B3LYP/6-31G* level. The results show that the barrier energy for the acylation reaction of NC1’ is lower than that of MC1 in the reaction with PBP2a. The mechanism of the reaction is discussed in details in this report. Keywords. Inhibit, PBP2a, b-lactam, nitrocefin, methicillin